18t+11v=w-3t

Simple and best practice solution for 18t+11v=w-3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18t+11v=w-3t equation:


Simplifying
18t + 11v = w + -3t

Reorder the terms:
18t + 11v = -3t + w

Solving
18t + 11v = -3t + w

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '3t' to each side of the equation.
18t + 3t + 11v = -3t + 3t + w

Combine like terms: 18t + 3t = 21t
21t + 11v = -3t + 3t + w

Combine like terms: -3t + 3t = 0
21t + 11v = 0 + w
21t + 11v = w

Add '-11v' to each side of the equation.
21t + 11v + -11v = -11v + w

Combine like terms: 11v + -11v = 0
21t + 0 = -11v + w
21t = -11v + w

Divide each side by '21'.
t = -0.5238095238v + 0.04761904762w

Simplifying
t = -0.5238095238v + 0.04761904762w

See similar equations:

| -3(x-4)=-24 | | 1+k=12.3 | | 5t+2=13 | | 39+9x=102 | | x=x^2+4x-1 | | (w-1)(2w+3)=5 | | (4x-30)=(3x+10) | | 7x-7=9x-15 | | 15=5(x-9) | | -6-6x=48 | | 45=-25+7x | | 3*3*3*3*3=9*9 | | 22-3g+5forg=4 | | 9.1+y=4.3 | | (2x-11)+3=16 | | 61+10x=-29 | | 3(3+0.9t)=2(-2.4t-3) | | 30-6x=60-26x | | 8-3(x-2)=2 | | 6x+8x=7x-14 | | 11+8x=59 | | 5z-8=3+7z | | 6x^2-x+1=2 | | 3x-37=6x+50 | | 10n-2n=4 | | 66-2x=75-3x | | x-1.22x=3.5 | | -3x+42=6x-129 | | 0.02x+1.5=2 | | 31+5x=9x-25 | | x*x=2xy+120 | | 5+8=b |

Equations solver categories